Desain Dan Analisis Sistem Kendali Pengereman Otomatis Pada Mobil City Car Manual Transmission - Doddy Satrya Perbawa (Jurnal Ilmiah SINUS, 2014)
The design of the automatic braking control system in the car city car manual transmission is applied to the car has a mass of 1090 kg empty and applied on a straight road with no twists and climbs as well as derivatives. The design of this system using ANFIS algorithm. The system implements momemtum formula mass force and acceleration are then applied in pascal law because the current legal system applying mechanical braking pascal. The system works triggered by several variables and the degree of membership of input variables are variables kecepaan, mass and distance, of the three input variables are obtained automatically from the sensor, the output generating braking pressure force that is triggered from the input variables. Variable output has berberda value corresponds to the value of input variables.Processing of input and output variables resulting from calculation pascal law, serve as training data for ANFIS, ANFIS processing using MATLAB. In this MATLAB rules and obtained a degree of membership value of the variable and variables derived from the FIS. From the results of FIS be tested by inserting some great input variables to determine the braking force that is done. Test data is applied in the CV AVR to do. CV AVR serves as a charging program for mikrokonroler using C language Results of CV AVR programs implemented in PROTEUS. Proteus serves as a prototype design of the system, there are several tools such as sensors and microcontrollers.Keywords: sensor, microcontroller, ANFIS, pressure, pascal law